Pengaruh Penambahan Tepung Daun Kelor (Moringa Oleifera L) terhadap Kadar Protein, Kapasitas Antioksidan dan Sensori Kukis Bebas Gluten - Adi, Maria Reynadia Binvenianinda Harsitaning; Puspawati, Gusti Ayu Kadek Diah; Arihantana, Ni Made Indri Hapsari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 1 (2024): Jurnal ITEPA, 2024)
Cookies are one of the most popular snack types because of their crunchy, sweet, and delicious taste. Cookies are generally made from wheat flour, meanwhile not everyone can consume wheat flour because of the gluten content in it, so it is necessary to make gluten-free cookies. Gluten-free cookies can be made from MOCAF and partly from composite flour with MOCAF and mung bean flour, but the protein content of the cookies produced is still below SNI. One of the local food ingredients that can be used to increase the protein content of cookies is Moringa leaf flour. Moringa leaves are known to be rich in protein and have antioxidant compounds necessary for health. The purpose of this study was to determine the effect of moringa flour addition on protein content, antioxidant capacity, and sensory of gluten-free composite cookies and to determine the right amount of moringa flour addition to produce cookies with the best characteristics. This study used a completely randomized design (CRD) with the treatment of moringa flour addition (K) with 8 levels, namely: 0%, 1.5%, 3%, 4.5%, 6%, 7.5%, 9%, and 10.5%. Each treatment was repeated 2 times to obtain 16 experimental units. The data obtained were then analyzed using variance analysis and if a significant effect was found, it was continued with Duncan's multiple range test. The results showed that the addition of moringa flour to the cookies was significant. The data obtained was then analyzed using variance analysis and if a significant effect was found, it was continued with Duncan's multiple range test. The results showed that the addition of moringa flour to gluten-free cookies had a significant effect (P<0.05) on protein content, antioxidant capacity, hardness, hedonic test of color, aroma, taste, overall acceptance, and taste scoring test. Treatment the addition of 3% moringa leaf powder gave the best cookies characteristic with the sensory criteria of color was slightly liked, aroma was liked, taste was liked, texture was slightly liked, typical moringa taste was slightly distinctive moringa, overall acceptance was liked. The protein of cookies gluten free with the addition of 3% moringa flour has met the SNI with a protein content of 8.69% and antioxidant capacity of 8.12 ppm of GAEAC.